2018
DOI: 10.1177/0885066617748596
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Risk Factors, and Outcome of Acute Kidney Injury in Neurocritical Care

Abstract: Acute kidney injury in neurocritical care has a high incidence and is a crucial risk factor for mortality independently of the underlying neurocritical condition. Sepsis is the main cause of AKI in this setting. Therefore, careful prevention of infectious complications and considering CKD in treatment decisions may lower the incidence of AKI and hereby improve outcome in neurocritical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 35 publications
4
27
0
Order By: Relevance
“…Our results were consistent with previous studies, reporting that first SCr value or assumed eGFR of 75 mL/min per 1.73 m 2 , in exchange of reduced selection bias and feasibility, may lead to misclassification in AKI diagnosis and staging [12, 19, 20]. These limitations have been recognized; nevertheless, the use of the surrogates is still widespread in AKI research [21-25]. In our patients, the eGFR 75 method overestimated disease incidence (19.3 vs. 14.…”
Section: Discussionsupporting
confidence: 90%
“…Our results were consistent with previous studies, reporting that first SCr value or assumed eGFR of 75 mL/min per 1.73 m 2 , in exchange of reduced selection bias and feasibility, may lead to misclassification in AKI diagnosis and staging [12, 19, 20]. These limitations have been recognized; nevertheless, the use of the surrogates is still widespread in AKI research [21-25]. In our patients, the eGFR 75 method overestimated disease incidence (19.3 vs. 14.…”
Section: Discussionsupporting
confidence: 90%
“…AKI during hospitalization after major surgical procedures is a risk factor for short-term mortality. Although several studies have reported a higher prevalence of AKI in various patient populations underwent various surgeries and confirmed the association of less severe AKI with short-term mortality, few studies have focused on AKI in the cohort of neurosurgical patients [9]. An unfavorable prognosis is often linked with neurocritical disease.…”
Section: Discussionmentioning
confidence: 99%
“…AKI after TBI has been reported developing in 7.6% to 23% patients and is correlated with mortality, functional outcome and length of hospital stay in TBI patients [4][5][6][7]. Mechanisms involved in development of AKI after TBI are diversified, which included systemic inflammation response, neuroendocrine hormone release, hypoperfusion and iatrogenic factors such as blood transfusion, drugs reducing intracranial pressure and usage of nephrotoxic antibiotics [8][9][10][11]. In view of the unfavorable outcome caused by AKI, exploring novel and available biomarkers to predict the possible occurrence of AKI in early stage and consequently avoid medical treatments adverse to normal renal function is beneficial for outcome and recovery of TBI patients.…”
Section: Introductionmentioning
confidence: 99%